Galactosylated bovine serum albumin nanoparticles for parenteral delivery of oridonin: tissue distribution and pharmacokinetic studies. (September 2014) - Li, Caiyun; Zhang, Dianrui; Guo, Yuanyuan; Guo, Hejian; Li, Tingting; Hao, Leilei; Zheng, Dandan; Liu, Guangpu; Zhang, Qiang
Abstract Bovine serum albumin (BSA) nanoparticle is a promising drug carrier system. Oridonin (ORI)-loaded galactosylated BSA nanoparticle (ORI-GB-NP) was prepared for liver targeting delivery of ORI. This work was designed to investigate the in vitro release, in vivo pharmacokinetics and tissue distribution of ORI-GB-NP. ORI-GB-NP was prepared by the desolvation method. The particle size of ORI-GB-NP was 172.0 ± 8.3 nm with narrow size distribution. The in vitro release of ORI-GB-NP exhibited biphasic drug release pattern with an initial burst release and consequently sustained release. Pharmacokinetic analysis displayed that ORI-GB-NP and ORI-loaded BSA nanoparticle (ORI-BSA-NP) could enhance the drug plasma level and prolong the circulation time in contrast with ORI solution. Meanwhile, compared with ORI-BSA-NP, ORI-GB-NP could deliver more ORI to liver and simultaneously reduce the toxicity of ORI to heart, lung and kidney. In conclusion, ORI-GB-NP could be a promising drug delivery system for liver cancer therapy.